Loss of histone macroH2A1 in hepatocellular carcinoma cells promotes paracrine-mediated chemoresistance and CD4+CD25+FoxP3+ regulatory T cells activation - Lo Re, Oriana; Mazza, Tommaso; Giallongo, Sebastiano; Sanna, Paola; Rappa, Francesca; Vinh Luong, Tu; Li Volti, Giovanni; Drovakova, Adela; Roskams, Tania; Van Haele, Matthias; Tsochatzis, Emmanuel; Vinciguerra, Manlio (Theranostics, 2020)
Rationale: Loss of histone macroH2A1 induces appearance of cancer stem cells (CSCs)-like cells in hepatocellular carcinoma (HCC). How CSCs interact with the tumor microenvironment and the adaptive immune system is unclear. Methods: We screened aggressive human HCC for macroH2A1 and CD44 CSC marker expression. We also knocked down (KD) macroH2A1 in HCC cells, and performed integrated transcriptomic and secretomic analyses. Results: Human HCC showed low macroH2A1 and high CD44 expression compared to control tissues. MacroH2A1 KD CSC-like cells transferred paracrinally their chemoresistant properties to parental HCC cells. MacroH2A1 KD conditioned media transcriptionally reprogrammed parental HCC cells activated regulatory CD4+/CD25+/FoxP3+ T cells (Tregs). Conclusions: Loss of macroH2A1 in HCC cells drives cancer stem-cell propagation and evasion from immune surveillance.
Keywords: regulace genové exprese u nádorů; Drug Resistance, Neoplasm; Paracrine Communication; parakrinní signalizace; Cell Line, Tumor; hepatocelulární karcinom; Interleukin-2 Receptor alpha Subunit; hepatocellular carcinoma; Gene Expression Regulation, Neoplastic; nádorové mikroprostředí; nádorové buněčné linie; lidé; Gene Knockdown Techniques; nádory jater; Carcinoma, Hepatocellular; chemorezistence; Metabolomics; chemoresistance.; forkhead transkripční faktory; receptor interleukinu-2 - alfa-podjednotka; metabolomika; Hyaluronan Receptors; Liver Neoplasms; histone macroH2A1; Forkhead Transcription Factors; T-Lymphocytes, Regulatory; Male; Neoplastic Stem Cells; adaptive immune system; genový knockdown; antigeny CD44; histony; lidé středního věku; Histones; Tumor Microenvironment; mužské pohlaví; regulační T-lymfocyty; glykolýza; Glycolysis; Middle Aged; nádorové kmenové buňky; Humans